GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 17 Jan 2019, 18:21

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Events & Promotions

Events & Promotions in January
PrevNext
SuMoTuWeThFrSa
303112345
6789101112
13141516171819
20212223242526
272829303112
Open Detailed Calendar
• The winning strategy for a high GRE score

January 17, 2019

January 17, 2019

08:00 AM PST

09:00 AM PST

Learn the winning strategy for a high GRE score — what do people who reach a high score do differently? We're going to share insights, tips and strategies from data we've collected from over 50,000 students who used examPAL.
• Free GMAT Strategy Webinar

January 19, 2019

January 19, 2019

07:00 AM PST

09:00 AM PST

Aiming to score 760+? Attend this FREE session to learn how to Define your GMAT Strategy, Create your Study Plan and Master the Core Skills to excel on the GMAT.

If 0 < x < 1 and y > 1, (√(x + y − 2√xy) + √(x + y + 2√xy) =

Author Message
TAGS:

Hide Tags

Math Expert
Joined: 02 Sep 2009
Posts: 52231
If 0 < x < 1 and y > 1, (√(x + y − 2√xy) + √(x + y + 2√xy) =  [#permalink]

Show Tags

19 Sep 2018, 23:50
00:00

Difficulty:

95% (hard)

Question Stats:

34% (02:00) correct 66% (01:33) wrong based on 111 sessions

HideShow timer Statistics

If $$0 < x < 1$$ and $$y > 1$$, $$\sqrt{x + y − 2\sqrt{xy}} + \sqrt{x + y + 2\sqrt{xy}} =$$

(A) √x
(B) 2√x
(C) √y +√x
(D) √y
(E) 2√y

_________________
Intern
Joined: 21 Feb 2018
Posts: 16
Re: If 0 < x < 1 and y > 1, (√(x + y − 2√xy) + √(x + y + 2√xy) =  [#permalink]

Show Tags

19 Sep 2018, 23:57
The equation can be written as √x-√y+√x+√y => 2√x
Option B

Sent from my ONE A2003 using GMAT Club Forum mobile app
CEO
Joined: 11 Sep 2015
Posts: 3331
If 0 < x < 1 and y > 1, (√(x + y − 2√xy) + √(x + y + 2√xy) =  [#permalink]

Show Tags

Updated on: 20 Sep 2018, 13:29
1
Top Contributor
Bunuel wrote:
If $$0 < x < 1$$ and $$y > 1$$, $$\sqrt{x + y − 2\sqrt{xy}} + \sqrt{x + y + 2\sqrt{xy}} =$$

(A) √x
(B) 2√x
(C) √y +√x
(D) √y
(E) 2√y

It's probably not immediately apparent, but x - 2√(xy) + y is a form of the SPECIAL PRODUCT x² - 2xy + y²
Notice that (√x - √y)² = (√x - √y)(√x - √y) = x - 2√(xy) + y
Likewise, (√x + √y)² = (√x + √y)(√x + √y) = x + 2√(xy) + y

So...
$$\sqrt{x + y − 2\sqrt{xy}} + \sqrt{x + y + 2\sqrt{xy}} =$$ (√x - √y)² + (√x + √y)²

-------------ASIDE-------------------------
IMPORTANT: before we conclude that (√x - √y)² = (√x - √y), we must recognize that, since 0 < x < y, √x - √y is NEGATIVE
Since the square root of a value cannot be NEGATIVE, it must be the case that (√x - √y)² = (√y - √x)
Here's an illustrative example:
(√1 - √9)² = (1 - 3)²
= (-2)²
= 4
= 2
Notice that √1 - √9 DOES NOT equal 2; it equals -2
However, √9 - √1 DOES equal 2
So, we can say that (√1 - √9)² = √9 - √1

Likewise, (√x - √y)² = (√y - √x)
-------------BACK TO THE QUESTION------------------------

$$\sqrt{x + y − 2\sqrt{xy}} + \sqrt{x + y + 2\sqrt{xy}} =$$ (√x - √y)² + (√x + √y)²
= (√y - √x) + (√x + √y)
= 2√y

RELATED VIDEO FROM OUR COURSE

_________________

Test confidently with gmatprepnow.com

Originally posted by GMATPrepNow on 20 Sep 2018, 08:03.
Last edited by GMATPrepNow on 20 Sep 2018, 13:29, edited 1 time in total.
CEO
Joined: 11 Sep 2015
Posts: 3331
Re: If 0 < x < 1 and y > 1, (√(x + y − 2√xy) + √(x + y + 2√xy) =  [#permalink]

Show Tags

20 Sep 2018, 13:35
Top Contributor
Bunuel wrote:
If $$0 < x < 1$$ and $$y > 1$$, $$\sqrt{x + y − 2\sqrt{xy}} + \sqrt{x + y + 2\sqrt{xy}} =$$

(A) √x
(B) 2√x
(C) √y +√x
(D) √y
(E) 2√y

Another (easier) approach is to just plug in values for x and y
How about x = 0.25 and y = 4

When we plug those values into the expression, we get:
$$\sqrt{x + y − 2\sqrt{xy}} + \sqrt{x + y + 2\sqrt{xy}} =$$ $$\sqrt{0.25 + 4 − 2\sqrt{1}} + \sqrt{0.25 + 4 + 2\sqrt{1}}$$
= 3/2 + 5/2
= 8/2
= 4

So, when x = 0.25 and y = 4, the given expression evaluates to 4
Now which of the following answer choices evaluates to 4 when x = 0.25 and y = 4??
(A) √0.25 = 0.5 NO GOOD
(B) 2√0.25 = (2)(0.5) = 1 NO GOOD
(C) √4 +√0.25 = 2 + 0.5 = 2.5 NO GOOD
(D) √4 = 2 NO GOOD
(E) 2√4 = (2)(2) = 4 GREAT!!!

Cheers,
Brent
_________________

Test confidently with gmatprepnow.com

CEO
Joined: 11 Sep 2015
Posts: 3331
Re: If 0 < x < 1 and y > 1, (√(x + y − 2√xy) + √(x + y + 2√xy) =  [#permalink]

Show Tags

20 Sep 2018, 13:38
Top Contributor
funsogu wrote:

Bunuel wrote:
If $$0 < x < 1$$ and $$y > 1$$, $$\sqrt{x + y − 2\sqrt{xy}} + \sqrt{x + y + 2\sqrt{xy}} =$$

(A) √x
(B) 2√x
(C) √y +√x
(D) √y
(E) 2√y

Turns out there's a big problem with B.
See my (edited) post above.

Cheers,
Brent
_________________

Test confidently with gmatprepnow.com

Joined: 18 Jun 2018
Posts: 103
Location: United States (AZ)
Concentration: Finance, Healthcare
Re: If 0 < x < 1 and y > 1, (√(x + y − 2√xy) + √(x + y + 2√xy) =  [#permalink]

Show Tags

20 Sep 2018, 13:42
Oh wow. I see my mistake now. Thanks GMATPrepNow

GMATPrepNow wrote:
funsogu wrote:

Bunuel wrote:
If $$0 < x < 1$$ and $$y > 1$$, $$\sqrt{x + y − 2\sqrt{xy}} + \sqrt{x + y + 2\sqrt{xy}} =$$

(A) √x
(B) 2√x
(C) √y +√x
(D) √y
(E) 2√y

Turns out there's a big problem with B.
See my (edited) post above.

Cheers,
Brent
Re: If 0 < x < 1 and y > 1, (√(x + y − 2√xy) + √(x + y + 2√xy) = &nbs [#permalink] 20 Sep 2018, 13:42
Display posts from previous: Sort by